The Association Between Long-Term Spicy-Food Consumption and the Incidence of Chronic Postsurgical Pain After Cesarean Delivery: An Observational Study - Wu Z; Yang M; Zhao P; Zou F; Peng J; Deng Q; Duan G; Li H (Journal of Pain Research, 2022)
Zhuoxi Wu,1,* Mi Yang,1,* Peng Zhao,1,2 Feng Zou,1 Jing Peng,1 Qiangting Deng,3 Guangyou Duan,4,* Hong Li1,* 1Department of Anesthesiology, Second Affiliated Hospital of Army Medical University, People’s Liberation Army of China, Chongqing, People’s Republic of China; 2Department of Anesthesiology, Chinese People’s Liberation Army of China (PLA) No. 964 Hospital, Changchun, People’s Republic of China; 3Editorial Office of Journal of Third Military Medical University, Army Medical University, People’s Liberation Army of China, Chongqing, People’s Republic of China; 4Department of Anesthesiology, the Second Affiliated Hospital, Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong Li; Guangyou Duan, Email lh78553@163.com; dgy1986anesthesia@126.comBackground: Our previous study found that a long-term diet incorporating spicy foods can reduce the human basal pain threshold. Capsaicin is the pungent ingredient in chili peppers. Transient receptor potential vanilloid type1 is the capsaicin receptor expressed in the oral cavity and is the primary sensory neuron of the “pain” pathway. Few studies have examined the association between long-term spicy diet and chronic postsurgical pain (CPSP). Women who underwent elective cesarean section (eCS) have consistent characteristics of CPSP. This study aimed to investigate the relationship between a long-term spicy diet and the incidence of CPSP after eCS.Methods: Participants were divided into a low frequency group (LF, numerical rating scale (NRS)< 5) for spicy food consumption and a high frequency group (HF, NRS≥ 5) by receiver operator characteristic analysis. The primary outcome was the incidence of CPSP three months after eCS. Propensity score matching (PSM) analysis was performed between the two frequency groups. Stepwise logistic regression analysis was then performed.Results: Of the 1029 enrolled patients, data from 982 were analyzed 3 months after eCS. After PSM, the incidence of CPSP in the HF group (30.1% [108/359]) was higher than that in the LF group (19.8% [71/359]; P = 0.001). Compared with the LF group, the risk of CPSP in the HF group increased 1.61 times by 3 months (95% CI 1.18– 2.20, P = 0.003). PSM results found that 1 year, the incidence of CPSP in the HF group (15.2% [56/369]) was higher than that in the LF group (8.1% [30/369], P = 0.003).Conclusion: With an NRS≥ 5 as a boundary, women who consumed spicy food ≥ 2 days/week were more likely to have CPSP than those who consumed spicy food < 2 days/week.Keywords: long-term spicy diet, chronic postsurgical pain, capsaicin, TRPV1, cesarean section